Penelitian Pendahuluan Pengaruh Daun Manggis sebagai Rodentisida Nabati pada Mencit Mus musculus Strain Balepsi - Agus Kardinan; Momo Iskandar; Mukhasim Mukhasim (Jurnal Perlindungan Tanaman Indonesia, 2000)
Research has been conducted at Pest and Disease Laboratory, Research Institute for Spices and Medicinal Crops, Bogor, during 1997-1998. The objective was to evaluate the possibility of Mangosteen (Garcinia mangostana) leaves to be used as botanical rodenticide which is tested to reproduction ability of mice Mus musculus. Eight to ten weeks old mice with the average weight of 25 gram were obtained from Research Institute for Livestock, Ciawi. Research was arranged at randomized block design, 8 treatments and 4 replications. Data was analyzed by determining the average value and their standard deviation values. Observations were done to the weight of testis, weight of embryo, number of embryo, volume of extracts drank by mice and mice behavior during experiment. Result revealed that there was no indication that the leaves extract affected the weight of testis, but it affected the number and weight of embryo. There was indication that mangosteen leaves acted as antifertility on mice. Giving leaves extract increased the total volume of extract drink. There was no abnormality at the activity of mice during experiment, included sex activity, poisonous symptoms and others.